GSTT1, GSTP1 and XPC genes are associated with longevity in an Italian cohort - Manuel Scarfò; Chiara Sciandra; Stefano Ruberto; Alfredo Santovito (Taylor & Francis Group, 2021)
Longevity is a complex process controlled by environmental and genetic factors. We evaluated the association of seven drug metabolising and DNA-repair gene polymorphisms with longevity in an Italian cohort. A sample of 756 subjects aged 18-98 was genotyped for CYP1A1 (rs1048943, A>G), GSTM1 (rs 1183423000, presence/absence), GSTT1 (rs1601993659, presence/absence), GSTP1 (rs1695, A>G), XRCC1 (rs1799782, C>T), XRCC1 (rs25489, A>G) and XPC (rs2228001, A>C) gene polymorphisms. The association between the studied gene polymorphisms and longevity was evaluated by dividing the sample into three age groups: 18-50, 51-85, and 86-98. We observed a significant decrease in the frequency of the GSTT1 null, GSTP1 G and XPC C alleles in the oldest group with respect to the youngest one. We also obtained the same results when dividing the sample into 18-85 and 86-98 age groups. The general linear model analyses confirmed a significant decreasing trend with age of the above mentioned alleles. We hypothesised that these minor alleles, being important in the sensitivity against the development of different types of cancer, may reflect a reduced life-expectancy in carrier subjects and may explain their significantly lower frequency observed among subjects belonging to the oldest age group.